TINJAUAN YURIDIS PERLINDUNGAN KONSUMEN TERHADAP PEREDARAN MAKANAN DAN MINUMAN KADALUARSA DI KOTA BAUBAU - Syarifuddin, Muhammad; Zamrud, Wa Ode; Taibu, Rachmat; Ningsih, Mega Lestari (Jurnal Ilmu Hukum Kanturuna Wolio, 2024)
This research uses a qualitative descriptive method, by collecting data through interview techniques and library data in the form of documents or literature related to the research topic of this thesis. Based on the research results obtained in this thesis, the author can draw the following conclusions: (1) Loka POM in monitoring food circulation uses 2 monitoring systems, namely pre-market supervision and post-market supervision. Apart from that, Loka POM also provides education to business actors, consumers, and the government to be wiser in producing, distributing and consuming products circulating in society. (2) Business actors who are proven to be still distributing expired food and drinks are obliged to provide compensation to consumers in the form of product replacements equivalent to their value, refunds for health care and even compensation.